Die huwelik as identiteitsmerker in die Ou Testament - Venter, Pieter M. (HTS teologiese studies, 2007)
Marriage as identity marker in the Old Testament The formularies used for consecrating marriages in the Nederduitsch Hervormde Church reflect this church’s view on matrimony. As the biblical bases of the formularies are deficient, new ways of exploring biblical information on this subject should be followed. This article proposes that data on marriage in the Bible always be used in conjunction with other concepts to form theological constructs to outline who God is and who his people are. It is always intended to be an identity marker to the members of the church. In the three Genesis cycles of Genesis 11:10-25:11; 25:12-35:29 and 36:1-50:26 heirship, marriage and land are used in an integrated construct to indicate the identity of the post-exilic community in Yehud. In the penitential prayers of Ezra 9:6-15 and Nehemia 9:5b-37 the concepts law, land and marriage are jointly used to depict the identity of the “real” Israel. The conclusion drawn from this investigation is that the Bible does not present models for marriage, but rather theological constructs to understand the relationship with the Lord in metaphorical terms and to reflect on the meaning of everyday life of that relationship including matrimony under ever changing social circumstances.